Transcardiac Endograft Delivery for Endovascular Treatment of the Ascending Aorta: A Feasibility Study in Pigs. (June 2015) - Wipper, Sabine; Lohrenz, Christina; Ahlbrecht, Oliver; Carpenter, Sebastian W.; Tsilimparis, Nikolaos; Kersten, Jan Felix; Detter, Christian; Debus, Eike S.; Kölbel, Tilo
Purpose: To compare the technical feasibility and hemodynamic alterations during antegrade transcardiac access routes vs conventional transfemoral access (TFA) for endovascular treatment of the ascending aorta in a porcine model. Methods: Antegrade transseptal access (TSA), transapical access (TAA), and TFA were used for implantation of custom-made endografts into the ascending aorta under fluoroscopy (6 pigs each). Hemodynamic parameters, myocardial and cerebral blood flow, and carotid artery blood flow were evaluated during baseline (T1), sheath advancement (T2), after sheath retraction (T3), and after endograft deployment (T4). Results: Endograft deployment was feasible in all animals; all coronary arteries remained patent. Hemodynamic parameters were comparable in all 3 study groups during all measurements. During T2, transient hemodynamic alteration occurred in all groups, with transient severe valve insufficiency in TSA and TAA reflected by the higher pulmonary to mean arterial pressure ratio (p<0.05) as compared with TFA. Values stabilized again at T3 and remained stable until T4. The innominate artery was partially occluded in 4 (TSA), 3 (TAA), and 5 (TFA) animals. There was no deterioration of myocardial or cerebral perfusion during the procedures. Endograft deployment and fluoroscopy times during TAA were shorter than in TSA and TFA. Conclusions: TSA, TFA, and TAA to the ascending aorta are feasible for endograft delivery to the ascending aorta in a porcine model. Transient hemodynamic instability in TSA and TAA recovered to near preoperative values. TAA appeared technically easier.